Chiral 1,2-Dialkenyl diaziridines: synthesis, enantioselective separation, and nitrogen inversion barriers - Zawatzky, Kerstin; Kamuf, Matthias; Trapp, Oliver (Chirality, 2015)
trans-1,2-Disubstituted diaziridines form stable enantiomers at ambient conditions because of the two stereogenic pyramidal nitrogen atoms. Functionalized trans-1,2-disubstituted diaziridines can be utilized as a chiral switching moiety between two enantiomeric states in more complex molecular structures. However, the synthesis of functionalized diaziridines is quite challenging, because of the limited tolerance of reaction conditions that can be applied. Here we present a strategy to make trans-1,2-disubstituted diaziridines accessible as versatile building blocks in C-C-bond formations, i.e., the Heck reaction, and therefore introducing aryl substituents. The synthesis of trans-1,2-dialkenyl diaziridines with terminal alkenyl substituents and their stereodynamic properties are described. Chirality 27:156-162, 2015. © 2014 Wiley Periodicals, Inc.
Gesehen am 21.07.2020
First published: 06 November 2014